Removal of Antibiotic Resistance From Municipal Secondary Effluents by Ozone-Activated Carbon Filtration - Spit, Tiza; van der Hoek, Jan Peter; de Jong, Coen; van Halem, Doris; de Kreuk, Merle; Perez, Bruno Bicudo (Frontiers in Environmental Science, 2022)
At wastewater treatment plants (WWTPs), additional steps are introduced for removal of organic micropollutants (OMPs) from the treated effluents, especially pharmaceutical residues. At the same time, a new concern is emerging: antibiotic resistance (AR).. This research studied the effect of ozonation, coagulation and granular activated carbon (GAC) filtration applied as tertiary treatment for the removal of OMPs and nutrients, on AR removal. Bacterial culture methods in selective media were used to screen for four different microorganisms: two fecal indicators (Escherichia coli (E. coli) and Enterococci) as antibiotic sensitive bacteria (ASB), and a resistant strain of each of these bacteria, namely Extended-Spectrum Beta-lactamase producing E. coli (ESBL-E.coli) and Vancomycin Resistant Enterococci (VRE) as antibiotic resistant bacteria (ARB). At laboratory scale, ozonation experiments (ozone dose 0.4-0.6 g O3/g DOC) and coagulation experiments using Polyaluminum chloride (PAX-214) and FeCl3 (coagulant dose 0.004-1 mM/l) were performed using secondary effluent from two municipal WWTPs. In addition in a pilot plant and full-scale plant ozonation (ozone dose 0.4 g O3/g DOC) and GAC filtration (empty bed contact time 15 min) were studied for AR removal. No significant differences were found between ARB and ASB removal for coagulation and ozonation which could indicate that ASB can be used as an initial proxy for ARB removal for these technologies. In the laboratory experiments, ozonation and coagulation showed a good removal of both ARB and ASB. However, the doses needed to reach 2-3 log removal were a factor 2.5-4 (ozonation) and 250 (coagulation) higher than applied for OMP removal (by ozonation) and phosphorus (P) removal (by coagulation). In the GAC filters, the risk of ARB enhancement occurred, especially in filters with a matured biology. Although these bacteria are not necessarily directly harmful, they can pass down their resistance to pathogenic bacteria via horizontal gene transfer.